Kinetics of thermal degradation of betacyanins, betaxantins and vitamin C in a juice-based drink beet (Beta vulgaris l.) and honey - Sánchez-Chávez, William (2015)
The kinetic of degradation betacyanins, betaxantins and vitamin C at 30 °C, 40 °C and 50 ºC was evaluated in a commercial beverage made of beet and honey, using the kinetic models of zero, first and second order; and Arrhenius model to evaluate the dependence of the rate of degradation with respect to temperature. It was determined that the degradation of the three compounds evaluated at the three tested temperatures followed a first order kinetics with a high correlation (R2 = 0.974, 0.98, 0.979). It was determined that the betacyanins and vitamin have a similar sensitivity to temperature; while betaxantins were more stable. Referring to the influence of temperature on the degradation rate, the activation energy and the reaction Q10 values were determined which confirm the increased stability of betaxantins regarding betacyanins and vitamin in the beverage of beet and honey.